Magnetic domains in hematite (?-Fe2O3) single crystal - Kokce, A. (My University, 1989)
Magnetic domain wall structure has been observed in ?-Fe2O3 single crystal using synchrotron radiation x-ray topography. The evaluation of the domain walls has been studied in varying external magnetic fields up to 50kAm-1. The observed walls have been identified as 180° weak ferromagnetic walls inclined to the basal plane. -Author
Keywords: domain theory; haematite; magnetism; wall structure